Evaluation of Fecal Incontinence in Pediatric Functional Constipation: Clinical Utility of Anorectal and Colon Manometry. Issue 3 (3rd March 2021) - Morera, Claudio; Nurko, Samuel; Rodriguez, Leonel
ABSTRACT: Objectives: The aim of the study is to evaluate the utility of motility studies in pediatric functional constipation with/without fecal incontinence. Patients and Methods: Patients with functional constipation and failure to conventional therapy undergoing colonic manometry (CM) and/or anorectal manometry (ARM) manometry were classified as functional constipation without fecal incontinence (FC) or with fecal incontinence (FCI). Clinical data, motility parameters, and treatment outcomes were compared. Results: A total of 280 were included, and all patients underwent CM (229 FC and 51 FCI) and 219 ARM. We found no difference in CM interpretation and presence of normal high amplitude propagating contractions (HAPCs) between groups; however, patients with FCI had higher frequency and presence of HAPCs and normal gastrocolonic meal response (GC). No CM parameter predicted outcomes. In FC, more patients with an abnormal CM responded to therapy compared to those with a normal study (79% vs 65% respectively, P = 0.04). FCI patients had lower median anal resting pressure compared to FC (49 vs 66 mmHg, respectively, P = 0.03); no other ARM parameter differentiated FC from FCI. We found no association between therapy response and ARM interpretation ( P = 0.847) or any ARM parameter. A multivariate analysis found only male gender was associated with FCI ( P < 0.001). Conclusions: FCI patients have higher frequency of normal CM parameters compared to FC, but overall interpretation was no different. CM helped predict response to therapy in FC but not in FCI. ARM demonstrated no added benefit in the evaluation of functional constipation with/without soiling. Patients with both normal ARM and CM had a lower response to therapy than those with abnormal studies.